Implementasi Prudential Principle Dalam Perlindungan Konsumen Pada Sistem Layanan Electronic Payment - Ardelia, Talita Adwa; Herta, Daiva Ebiandre (Media Hukum Indonesia (MHI), 2025)
The development of digital technology has driven the rapid growth of electronic payment (e-payment) service systems as an integral part of modern economic transactions. However, the convenience offered is also accompanied by various risks, both in terms of data security, information transparency, and protection of consumer rights. This study aims to analyze the implementation of the prudential principle in consumer protection efforts in the e-payment service system. The prudential principle, which prioritizes the principles of prudence, integrity, and risk management, is an important foundation in building consumer trust and creating stability in the digital financial system. The research method used is normative juridical with a statutory regulatory approach and literature studies. The results of the study show that although regulations related to e-payment have accommodated the principles of prudence, their implementation in the field still faces challenges, such as lack of information transparency, weak supervision of organizers, and low consumer digital literacy. Therefore, it is necessary to strengthen regulations, stricter supervision by relevant authorities, and increase consumer education to optimize protection in the e-payment ecosystem based on the prudential principle